THE EFFECT OF NACL AND KOH SOLUTION VARIATIONS ON HYDROGEN PRODUCTIVITY AND CORROSIVITY IN WET HHO GENERATORS USING SS316L ELECTRODES - Akmal Tri BasunJaya; Bernardus Crisanto Putra Mbulu; Antonius Prisma Jalu Permana (Mechanical, Energy and Material (METAL), 2025)
The increasing energy demand due to population growth and industrial development has driven the search for clean and renewable alternative energy sources. One promising solution is hydrogen-based energy through water electrolysis, which produces HHO gas (a mixture of hydrogen and oxygen).  The efficiency of the electrolysis process is significantly influenced by the type and concentration of the electrolyte solution used, such as NaCl and KOH, as well as the electrode material here, stainless steel SS316L. This study shows that increasing the mass of the electrolyte solution enhances hydrogen production. NaCl with a mass of 153 grams produced 1,509 ppm of hydrogen at the high-variable setting, while KOH with a mass of 147 grams produced up to 2,320 ppm. However, KOH also caused higher corrosion levels, reaching 0.117 grams in the high-variable setup, compared to NaCl at 0.038 grams. The Cl⁻ and OH⁻ ions in the electrolyte are highly reactive and contribute to electrode surface degradation. Furthermore, the electrode position affects hydrogen productivity, where closer proximity to the power source improves reaction efficiency. Therefore, the selection of electrolyte type and the optimization of the electrolysis system configuration are crucial in the development of efficient hydrogen production technology.